Incorporating Sex as a Biological Variable into Clinical and Translational Research Training - Kantarci, Kejal (J Womens Health (Larchmt), 2020)
Incorporating sex as a biological variable (SABV) into basic and medical research requires a deliberate plan that weaves concepts of basic genetics, cellular and molecular physiology, and pharmacology into translational medicine. An R4 approach (Right content to the Right learner at the Right time with the Right modality) allows for content to be available in a variety of formats that reinforces the concepts at staged levels of integration. Weaving SABV throughout the varied formats of the R4 approach within the Clinical and Translational Research Training Programs, into the mentoring and training of scholars in NIH Building Interdisciplinary Careers in Women's Health (BIRCWH), and into the Career Enhancement Core of the Specialized Centers of Research Excellence (SCORE) on sex differences through curriculum, case-based approach and journal clubs, and workshops ensures that learners grasp its fundamental relevancy to their own research and beyond. In addition, the collaborative work among the BIRCWH and SCORE programs brings collective expertise from centers around the United States to individual programs through development of best practices and materials. These collective efforts assure that the next generation of basic, clinical, and translational scientists will bring the dimension of SABV into their research and clinical practice.